Results of a healthcare organisation model for COVID-19 in haemodialysis in a tertiary hospital and its subsidized centres() - Sánchez-Pérez, Pilar (Nefrología (English Edition), 2020)
The experience of a tertiary hospital and four hemodialysis centers attached to it during the COVID-19 epidemic is described. The organization of care that has been carried out and the clinical course of the 16 cases of COVID-19 in hemodialysis patients are summarized. The joint application of measures, including patient screening, the early investigation of possible cases, the isolation of confirmed, investigational or contact cases, as well as the use of individual protection measures, has enabled the epidemic to be controlled. The clinical course of these 16 patients is compared with the series published by the Wuhan University Hospital and with the data from the Covid-19 infection registry of the Spanish Society of Nephrology. In our experience, and unlike what was reported by the Wuhan Center, COVID-19 disease in hemodialysis patients is severe in a significant percentage of cases, and high lethality is mostly caused by the infection itself. Measures to contain the epidemic are effective.